Research on Mechanism and Control Technology of Rib Spalling in Soft Coal Seam of Deep Coal Mine - Shaobo Li; Lei Wang; Chuanqi Zhu; Qihan Ren (Advances in Materials Science and Engineering)
In order to solve the difficult problem of coal wall spalling of soft seam in deep mining, the occurrence mechanism of coal wall spalling in deep mining is studied based on the limit equilibrium theory of D-P criterion. Through the analysis of the formula of plastic zone, it can be concluded that the coal wall spalling of soft coal seam is related to mining depth, mining height, stress concentration factor, internal friction angle of coal, cohesion, and the compressive strength of coal body. Also, the change of uniaxial compressive strength of soft coal with different moisture content is studied through laboratory experiments. The experimental results show that the uniaxial compressive strength of soft coal reaches the maximum value when the moisture content is about 3.3%. The comprehensive research shows that the cohesion and strength of coal mass can be improved by increasing the working resistance of support, water injection in advanced deep-hole coal seam of two roadways, and pre-grouting in shallow hole of coal wall. The control measures can effectively control the coal wall spalling of soft coal seam. The research results have important guiding significance for safe and efficient mining of soft coal seam.